Etched graphene oxide hybrid membrane for aqueous organic flow battery, preparation method and application
The hybrid film prepared by doping the secondary oxidized graphene oxide with sulfonated polyether ether ketone, the problems of low efficiency of traditional RFB coulombs and unstable separator performance are solved, and more efficient ion conduction and selectivity are achieved , improves the overall performance of the flow battery.
Patent Information
- Application Number
- CN202411440506.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-15
AI Technical Summary
Due to the inherent characteristics of inorganic redox species, traditional aqueous redox flow batteries (RFBs) are difficult to meet the large-scale and sustainable energy storage due to the inherent characteristics of inorganic redox species. need.
Using hybrid films, the graphene oxide with secondary oxidized sulfuric acid as an inorganic filler is doped with easy-to-synthesis and low-cost sulfonated polyether ether ketone (SPEEK) to form graphene oxide material with surface pores. To improve the mechanical strength, hydrophilicity and voltage efficiency of the film.
By introducing etched graphene oxide materials, the ion selectivity and ion conductivity of the hybrid film are optimized, which significantly improves the performance of water-based organic flow batteries, including all-vanadium flow batteries, zinc-iron flow batteries, etc. application efficiency. .
Smart Images

Figure CN119505512A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a hybrid membrane for an aqueous organic liquid flow battery, a preparation method and application thereof, and belongs to the technical field of aqueous organic liquid flow batteries. Background Art
[0002] The rapid development of human society and economy has led to a sharp increase in energy demand. The massive consumption of fossil energy has led to serious environmental and social problems. With the global "carbon peak" and "carbon neutrality" goals, the demand and utilization of renewable energy have received special attention. Wind and solar energy have been greatly developed as alternative energy sources due to their cleanliness and renewability. However, due to the natural randomness and intermittent characteristics of renewable alternative energy, large-scale cost-effective energy storage systems have received considerable attention. Large-scale energy storage technologies include physical energy storage, electromagnetic energy storage, electrochemical energy storage, and thermal energy storage (TES). Among the energy storage devices that have been successfully applied in practice, redox flow batteries (RFBs) have the advantages of high safety, long cycle life, and freedom of site selection, and are considered to be the energy storage device with the greatest potential in large-scale energy storage applications.
[0003] Most of the widely studied aqueous RFBs (ARFBs), such as the all-vanadium, iron / chromium, and zinc / bromine RFB systems, are based on inorganic redox pairs, especially metal-based electroactive species. Due to the inherent characteristics of inorganic redox species, the widespread adoption of traditional ARFBs is limited by relatively low Coulombic efficiency and high system cost. The utilization of redox-active organic species in aqueous redox flow batteries holds great promise for large-scale and sustainable energy storage. Sulfonated polyetheretherketone materials are used in the field of RFBs due to their advantages such as easy synthesis and low cost, but their performance is seriously affected by the degree of sulfonation. When the degree of sulfonation is high, its ion selectivity is low; when the degree of sulfonation is low, its ion conductivity is low. Therefore, the development of a battery separator with stable performance, high efficiency and low cost is of long-term significance to the development of flow batteries. Summary of the invention
[0004] The present invention is to solve the problems raised in the above background technology and provides a hybrid membrane for aqueous organic liquid flow battery, a preparation method and use thereof
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A hybrid membrane for an aqueous organic liquid flow battery comprises an inorganic filler and a polymer substrate casting solution, wherein the inorganic filler is graphene oxide secondary oxidized by sulfuric acid, and the polymer substrate is sulfonated polyetheretherketone (SPEEK) which is easy to synthesize and has a low cost, and the sulfonation degree ranges from 50% to 75%. The sulfonated polyetheretherketone (SPEEK) casting solution is doped with etched graphene oxide (PGO) filler to prepare the membrane.
[0007] Etched graphene oxide materials are used to improve the mechanical strength, hydrophilicity and voltage efficiency of the hybrid membrane.
[0008] The weight ratio of the etched graphene oxide in the polymer substrate is 0.1%-10%, preferably 0.5%-4%; the thickness of the hybrid film is 10-70 μm, preferably 20-40 μm.
[0009] A method for preparing a hybrid membrane for an aqueous organic flow battery comprises the following steps:
[0010] S1: adding sulfuric acid and graphene oxide in a mass volume ratio of 0.008-0.02:3-5 to a reaction solvent, stirring vigorously until completely mixed, and then transferring to a high-pressure reactor to react for 6-20 hours at 60-120° C., washing with water to remove the acid, and freeze-drying to obtain etched graphene oxide;
[0011] S2: mixing the etched graphene oxide filler with the sulfonated polyetheretherketone casting solution in proportion;
[0012] S3: adding ball mill beads to the mixed solution, stirring evenly and removing bubbles before pouring the solution on the substrate;
[0013] S4: Drying the film obtained on the substrate to obtain a hybrid film.
[0014] In step S1, the solvent used is DMF, and the deacidification process uses deionized water.
[0015] A hybrid membrane for aqueous organic liquid flow battery and its application in liquid flow battery.
[0016] The liquid flow battery is an aqueous organic liquid flow battery with a positive electrode of ferrocyanide and a negative electrode of a phenazine derivative.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The present invention prepares a membrane by doping a graphene oxide material with surface pores with sulfonated polyetheretherketone, and the obtained hybrid membrane performance includes optimizing the ion selectivity and ion conductivity of the diaphragm, thereby developing a new generation of high-performance PEM for the application of RFB systems. In the present invention, by adding a graphene oxide material with surface pores to a polymer substrate, the application of the hybrid membrane in the field of redox flow batteries including all-vanadium flow batteries, zinc-iron flow batteries, and aqueous organic flow batteries can be improved. By introducing an etched graphene oxide material, its oxygen-containing groups can form hydrogen bonds with the sulfonic acid groups in the polymer substrate, and the pores remaining on the surface after etching, the ion selectivity and ion conductivity of the hybrid membrane can be effectively enhanced. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 a) Infrared images of GO and PGO b) Raman images of GO and PGO c) TEM image of GO d) TEM image of PGO
[0020] Figure 2 TEM characterization of graphene oxide obtained under different etching conditions
[0021] Figure 3 This is the cross-sectional electron microscope image of SPEEK / PGO-X (X=0, 0.5, 1, 2, 3, 4%)
[0022] Figure 4 a) proton conductivity, b) water absorption and swelling rate, c) tensile strength and d) organic permeability and selectivity of SPEEK / PGO-X (X = 0, 1, 2, 3, 4, 5%)
[0023] Figure 5 Schematic diagram of flow battery a) Performance diagram of aqueous organic flow battery, b) CE, c) VE, d) EE at 20-100 mA cm -2 Current density
[0024] Figure 6 Aqueous organic flow battery cycle test diagram a) CE, b) EE (current density 80mAcm -2 )
[0025] Figure 7 This is the battery performance diagram of the SPEEK / GO-X membrane comparison experiment DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The present invention discloses a method for simply and quickly etching graphene oxide (GO) and its application. The present invention is sulfuric acid etching, which exposes more oxygen-containing groups through secondary oxidation with sulfuric acid, penetrates and forms holes on the surface of the two-dimensional sheet, and provides more ion transmission channels. Sulfonated polyetheretherketone (SPEEK) with low cost and simple synthesis process is selected as the polymer substrate.
[0028] Etched graphene oxide (PGO) is used as a filler and doped with it to prepare a flow battery separator. On the one hand, the etched graphene oxide contains more exposed oxygen-containing groups, which is more conducive to forming hydrogen bonds with the sulfonic acid groups in the polymer substrate, promoting ion transport; on the other hand, the two-dimensional sheets of graphene oxide hinder ion transport. Etching can fragment them into smaller sizes and penetrate the surface to form pores. The surface pores provide more transmission channels, while retaining the high ion selectivity of graphene oxide and improving its ion conductivity, thereby achieving dual performance improvements of the hybrid membrane.
[0029] The PGO used in the following examples is a hydrophilic material containing surface pores, and graphene oxide is a stable material resistant to strong acids and alkalis, and can be used in aqueous organic flow batteries. The oxygen-containing groups on the edge of GO itself can transfer ions, and the oxygen-containing groups exposed by etching form a hydrogen bond network with the sulfonic acid groups in the polymer substrate, which can promote ion transfer. The surface pores retained after etching can further enhance the ion transfer capacity.
[0030] For the material of the present invention, the sulfonation degree of sulfonated polyetheretherketone is controlled at 60%-70%. Too high or too low sulfonation degree has an impact. When the sulfonation degree is high, its ion selectivity is low; when the sulfonation degree is low, the ion conductivity is low.
[0031] Example 1
[0032] Synthesis and Etching of Graphene Oxide
[0033] Synthesis of GO: Mix 2g of graphite powder and 2g of sodium nitrate in a 500ml beaker, add 96ml of concentrated sulfuric acid and stir evenly, add 12g of potassium permanganate in four times, and control the time of each addition to about 10min, and the speed is 230r / min. Use a syringe pump device to add 80ml of water twice, set the program to extract 40ml from a 60ml capacity, the injection speed is 2ml / min, control the temperature at 60-70℃, and stop adding water in time according to the temperature. Also use a syringe pump to add 200ml of water (added in 5 times). Add 10ml of hydrogen peroxide, which produces a lot of bubbles in the process, and stir for about 30min. The product is centrifuged and washed 4-5 times, then added 100ml of concentrated hydrochloric acid and left to stand in the beaker for 24h, the supernatant is taken and centrifuged and washed until neutral, and freeze-dried to obtain GO.
[0034] Synthesis of PGO: GO and sulfuric acid (3M) were added to the reaction bottle at a mass volume ratio of 0.01:4, stirred vigorously until completely mixed, and transferred to a high-pressure reactor for reaction at 100°C for 15 hours. After sedimentation, a large amount of acid in the supernatant was removed, and the product was centrifuged and washed several times after etching to remove residual acid, and the product PGO was obtained after freeze-drying.
[0035] The infrared image, Raman image and TEM image of the product are as follows: Figure 1 shown.
[0036] The characterization results of graphene oxide obtained under different etching conditions are shown in Figure 2 It can be seen that if the etching time is too short, the open-pore structure cannot be formed, and if the etching time is too long, the structure of the nanosheet will be destroyed.
[0037] Example 2
[0038] Preparation of SPEEK / PGO hybrid membrane
[0039] SPEEK is prepared by adding peek powder into a 1000 ml three-necked flask, reacting in a water bath, and then adding 98 wt.% sulfuric acid for sulfonation for 5 hours.
[0040] Dissolve SPEEK and PGO in N,N-dimethylformamide at a concentration ratio of 1.5g / 10ml, and weigh a certain volume of solution according to the mass fraction ratio to mix. Ultrasonicate, ball mill, and mix the mixed casting liquid to form a uniform SPEEK / PGO casting liquid. Use a 400mm scraper to scrape it on a glass plate, then transfer it to an oven, set the temperature from 60°C to 100°C until it is completely dried. The configured hybrid membrane is represented as SPEEK / PGO-X, where X represents the mass ratio of PGO to the whole material.
[0041] As a comparison, a GO hybrid polymer membrane without etching was prepared for battery performance testing, SPEEK / GO-X. When making the comparison, the amount of GO added to the polymer membrane was 0.5%-4%.
[0042] Test Method
[0043] Swelling rate and water absorption
[0044] The SR (swelling rate) and WU (water absorption rate) of the membrane are obtained by the following two equations:
[0045]
[0046] Where d and W are the diameter and mass of the membrane in wet and dry states, respectively.
[0047] The test results are as follows Figure 4 As shown in b).
[0048] Mechanical properties
[0049] At a pulling speed of 5 mm min -1The mechanical properties of the film were obtained on a universal testing machine. The sample was cut into strips of 35 mm × 10 mm. The water on the surface of the wet film was wiped off before testing. In order to reduce the test error, three samples were tested for each film, and the obtained data were averaged. The tensile strength of the film sample was calculated as follows:
[0050]
[0051] In the formula, F Max is the maximum tension; W and D are the width and thickness of the sample film, respectively. The test results are shown in Figure 3 As shown in d).
[0052] Proton transfer rate
[0053] The proton transfer rate of the membrane was measured by AC impedance spectroscopy on an electrochemical workstation (Solartron analytical 1470E+1260A). The sample was sandwiched between two round titanium sheets, which were fixed with button cell clips. The test frequency was 10 3 Up to 10 6 The AC amplitude is 5mV. The proton transfer rate of the membrane is measured using the latest method of Professor Li's team, and the calculation formula is as follows:
[0054]
[0055] Where σ is the proton transfer rate of the membrane. L is the thickness of the sample. R is the impedance of the membrane. A is the effective area of the membrane, that is, the area of the titanium sheet. The test results are as follows: Figure 4 As shown in a).
[0056] The membrane surface resistance can be calculated by the following formula:
[0057] RA=R×A
[0058] R A is the membrane surface resistance.
[0059] Ion permeation rate and ion selectivity
[0060] The effective area is 0.78 cm 2 The H-type diffusion cell was tested. One side of the diffusion cell was filled with 50mL of 1M KOH+0.1M BHPC solution or 1M KOH+0.2M potassium ferrocyanide solution, and the other side of the diffusion cell was filled with the same volume of 1M KOH solution. Magnetic stirring was used to reduce concentration polarization during the test. Samples were taken from the aqueous solution every 12 hours, and the absorbance was measured at 315nm / 323nm using a UV-visible spectrophotometer. The standard absorbance / concentration curve was used to determine the BHPC organic matter or F e 2+The penetration rate of BHPC organic matter and ferrocyanide can be calculated by the following formula:
[0061]
[0062] Where V B The volume of 1M KOH+0.1M BHPC solution is 50ml in this experiment; C B (t) is the concentration of BHPC organic matter in 1M KOH+0.1M BHPC solution at time t; C A is the concentration of BHPC organic matter in 1M KOH+0.1M BHPC solution. If the test time is not too long, it can be considered as a constant to simplify the calculation; A and L are the effective membrane area and membrane thickness respectively; P is the permeation rate of BHPC organic matter. The results are shown in Figure 4 As shown in d).
[0063] Ion selectivity is defined as the proton transfer rate vs. BHPC organic matter - The ratio of the permeability rates is calculated as follows:
[0064]
[0065] Basic Characterization of Membranes
[0066] Figure 3 This is a photo of the diaphragm cross section. Figure 4 a) proton conductivity, b) water absorption and swelling rate, c) tensile strength and d) organic permeability and selectivity of SPEEK / PGO-X (X = 0, 1, 2, 3, 4, 5%)
[0067] Single cell performance
[0068] The performance of the AORFBs was tested using a homemade aqueous organic flow battery system consisting of a membrane (with an effective distance of 10.5 cm) 2 ), a carbon felt electrode, a carbon felt electrode, two graphite plate current collectors and a pair of shells. The membrane separates the negative electrolyte (10ml 1M KOH + 0.1M BHPC) and the positive electrolyte (40ml 1M KOH + 0.2M potassium ferrocyanide) and is sandwiched between the two electrodes. For the charge and discharge tests, the cut-off voltages for charge and discharge were 1.7V and 0.8V, respectively, and the current densities tested were 20, 40, 60, 80 and 100mAcm -2 For the cycling test, the constant current density was 80 mA cm -2 Tested at the same cut-off voltage. During the test, nitrogen protection was used. The coulombic efficiency (CE), voltage efficiency (VE) and energy efficiency (EE) of the battery were calculated by the following formula:
[0069]
[0070] Among them C d and C c are the discharge capacity and the charge capacity respectively; E d and E c They are discharge energy and charge energy respectively.
[0071] The AORFBs performance of the SPEEK / PGO-X hybrid membranes was evaluated (at 20–100 mA cm -2 under a series of current densities). Figure 5 , 6 As shown in the figure, the battery performance (CE, VE) of the SPEEK membrane can be significantly improved by doping with PGO. This result shows that incorporating etched graphene oxide materials into polymers can effectively improve battery performance. Figure 5 It can be seen that when the doping amount of PGO is 2%, the performance parameters of the battery are optimal. This is because if the amount added is small, the proton transfer rate cannot be effectively improved, and if the doping amount is too large, it will affect the surface structure of the membrane layer and reduce the battery performance. In addition, when etching PGO, if the etching time is too short, the surface structure of GO cannot be significantly changed, and if the etching time is too long, it will cause its structure to be destroyed, which will also affect the battery performance.
[0072] In addition, the comparative experimental results of SPEEK / GO-X membrane are as follows Figure 7 , compared with SPEEK / PGO-X, its coulombic efficiency and voltage efficiency both decreased.
[0073] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-limiting from any point of view, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention, and any reference numerals in the claims should not be regarded as limiting the claims involved.
Claims
1. A hybrid membrane for an aqueous organic flow battery, characterized in that: The invention comprises an inorganic filler and a polymer substrate, wherein the inorganic filler is graphene oxide (GO) after etching, and the inorganic filler is dispersed in the polymer substrate.
2. The hybrid membrane for aqueous organic flow battery according to claim 1, characterized in that: The etching treatment refers to graphene oxide treated with sulfuric acid etching.
3. The hybrid membrane for aqueous organic flow battery according to claim 1, characterized in that: The polymer substrate is sulfonated polyetheretherketone, and the sulfonation degree ranges from 50% to 75%.
4. The hybrid membrane for aqueous organic flow battery according to claim 1, characterized in that: Sulfonated polyetheretherketone casting solution is doped with etched graphene oxide filler to prepare the film.
5. The hybrid membrane for aqueous organic flow battery according to claim 1, characterized in that: The weight ratio of the graphene oxide (GO) after etching in the polymer substrate is 0.1%-10%, preferably 0.5%-4%.
6. The hybrid membrane for aqueous organic flow battery according to claim 1, characterized in that: The thickness of the hybrid film is 10-70 μm, preferably 20-40 μm.
7. The method for preparing a hybrid membrane for an aqueous organic flow battery according to claim 1, comprising the following steps: S1: Add sulfuric acid and graphene oxide to a reaction solvent, stir vigorously until completely mixed, then transfer into a high-pressure reactor to react for 6-20 hours at 60-120° C., wash away the acid with water, and freeze-dry to obtain etched graphene oxide; S2: mixing the etched graphene oxide filler with the sulfonated polyetheretherketone casting solution in proportion; S3: adding ball mill beads to the mixed solution, stirring evenly and removing bubbles, then pouring the solution and scraping it on the substrate; S4: Drying the film obtained on the substrate to obtain a hybrid film.
8. The method for preparing a hybrid membrane for an aqueous organic flow battery according to claim 3, characterized in that: In step S1, the mass volume ratio of sulfuric acid to graphene oxide is 0.008-0.02:3-5, and the reaction condition of the high-pressure reactor is 60-120° C. for 6-20 hours; In step S2, the solvent used in the sulfonated polyetheretherketone casting solution is DMF, and deionized water is used in the deacidification process.
9. Use of the hybrid membrane for aqueous organic liquid flow battery according to claim 1 in a liquid flow battery.
10. The use of a hybrid membrane for an aqueous organic liquid flow battery in a liquid flow battery according to claim 5, characterized in that: The liquid flow battery is an aqueous organic liquid flow battery with a positive electrode of ferrocyanide and a negative electrode of a phenazine derivative.
Citation Information
Patent Citations
Pteridine aqueous organic redox flow battery
CN110265694A
Preparation method of porous graphene oxide nanofiltration membrane
CN112915787A
Composite membrane material with wide pH adaptability for aqueous organic flow battery as well as preparation and application of composite membrane material
CN115498231A
KR20190000959A